INVESTIGATION OF EATING AND PHYSICAL ACTIVITY HABITS IN BALIKESİR HIGH SCHOOL STUDENTS - Yusuf Alper; Zekine Pündük; Fahri Akçakoyun; Zekeriya Göktaş (ümit doğan üstün, 2017)
The aim of this study was to investigate the effect of the nutrition and physical exercise habits change on overweight in Balikesir Science High School students. Eighty-five volunteered students (46 girls and 39 boys), participated in this study. The participant's nutrition habits and physical characteristics were analyzed twice in three years, 1st when participants were 15 years old (grade 9) 2nd when they were 18 years old (grade 12). The study results showed increase in body weight, height and body mass index (BMI) in grade 12 compared to grade 9, but no increase in waist/hip ratio. The participation in physical activity and physical activity duration was declined in grade 12 (p=0.000, p=0.004 respectively). When the scale mean scores evaluated it was found that, the nutrition habit risk score increased except question 2 and 5. In addition, boys more participated in physical activity than girls (p=0.001) when they were in grade 9, but in grade 12 this physical activity participation level more decreased in girls compared to boys (p=0.04). In conclusion, this study results indicated that in grade 12 or 18 years old bad nutrition habits increased and physical exercise participation level decreased with school and exam factors.